THE ESSENCE OF INTANGIBLE FACTORS AND THEIR INFLUENCE ON THE DEVELOPMENT OF THE REGIONAL ECONOMY - A. Nazarov (Вестник университета)
The article discusses the content and essence of the intangible factors, their influence on the development of the regional economy. Analyzes the peculiarities of development of the intangible factors through system innovation and technological development on the example of Moscow region.